Primary esophageal malignant melanoma successfully treated with anti-PD-1 antibody for retroperitoneal recurrence after esophagectomy: A case report. (2020) - Endo, Fumitaka; Akiyama, Yuji; Onishi, Masazumi; Fujisawa, Ryosuke; Sasaki, Noriyuki; Nikai, Haruka; Baba, Shigeaki; Sugimoto, Ryo; Kimura, Toshimoto; Takahara, Takeshi; Iwaya, Takeshi; Otsuka, Koki; et al.
Highlights: Primary malignant melanoma of the esophagus (PMME) is a rare disease with a poor prognosis. There are few reports of treatment with the anti-programmed cell death 1 antibody, nivolumab for PMME. We report a case of retroperitoneal recurrence of PMME successfully treated with nivolumab. Abstract: Introduction: Primary malignant melanoma of the esophagus (PMME) is a rare disease with a poor prognosis. Here, we report a case of retroperitoneal recurrence of PMME successfully treated with the anti-programmed cell death 1 antibody, nivolumab. Presentation of case: A 70-year-old male with dysphagia was referred to our hospital. Esophagogastroscopy showed an elevated tumor in the lower thoracic esophagus. A histopathological examination of the biopsy revealed poorly differentiated squamous cell carcinoma. The patient was diagnosed with clinical T3N1M0 stage III esophageal squamous cell carcinoma and was treated with neoadjuvant chemotherapy followed by radical esophagectomy. A postoperative histopathological examination revealed that atypical cells with a brown pigment were scattered in the tumor. Immunohistochemical staining demonstrated positive expression of human melanoma black 45, melan A, and S100. A pathological diagnosis of PMME was confirmed. Sixteen months after surgery, abdominal computed tomography revealed solitary retroperitoneal recurrence in the lateral portion of the ascending colon. Fluorine-18 fluorodeoxyglucose positron emission tomography (PET) showed hypermetabolic accumulation with a maximum standardized uptake value of 5.8. The patient was treated with nivolumab (240 mg) every two weeks. After eight courses of nivolumab, abnormal accumulation of the retroperitoneal mass disappeared on PET, and this therapeutic effect continued for 20 months. Conclusions: Nivolumab was effective for recurrence of PMME in our case. There are few reports of treatment with nivolumab for PMME. Further studies are necessary to establish the usefulness of nivolumab for PMME in the future.